2019
DOI: 10.1002/cncr.32384
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of cancer among sexual and gender minority populations: Where are we and where do we need to go?

Abstract: Systematic collection of high‐quality data on sexual and gender minority status is fundamental to assessing and monitoring the burden of cancer in this understudied and underserved population. The majority of hospitals do not collect these data, and physicians' offices do not perceive the data to be medically relevant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Considering the large population and diversity of SGM status within the city, San Francisco could be an ideal location to further investigate the relationship between gender identity, sexual orientation, and breast cancer risk and mortality, and to tailor interventions toward non-heterosexual women. Incorporation of sexual gender minority data into population-based cancer registries will be crucial to better document the burden of cancer in this underserved population (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…Considering the large population and diversity of SGM status within the city, San Francisco could be an ideal location to further investigate the relationship between gender identity, sexual orientation, and breast cancer risk and mortality, and to tailor interventions toward non-heterosexual women. Incorporation of sexual gender minority data into population-based cancer registries will be crucial to better document the burden of cancer in this underserved population (33,34).…”
Section: Discussionmentioning
confidence: 99%
“…3 However, population-based cancer registry data have not been fully used in assessing the cancer disparities among GMIs, 1 even though population-based cancer registries do collect sex information beyond male and female. 4 We found one previous study using national cancer surveillance data that identified lung cancer as the most common cancer for transgender indivduals. 5 We hypothesized that the vulnerable GMIs may be subject to identifiable disparities in lung cancer care and outcomes.…”
mentioning
confidence: 86%
“…[66][67][68] For example, the term "transsexual" was widely used in the past decade but is now considered offensive by some, and the more inclusive term "transgender" is preferred. 69,70 Terminology may also vary throughout the United States; for example, people on the west and east coasts of the United States may be likely to use the term "queer" to describe their sexual orientation, whereas in the South the term may be considered insulting. 71 Generational variations also exist in the use of SGM terminology.…”
Section: Recommendations For Oncology Institutionsmentioning
confidence: 99%